Creative economy and Covid-19: the post crisis trends in Brazil and globally - Gammal Zeitune, Leonardo Jacques (Diálogo com a Economia Criativa, 2020)
Abstract This article aims to introduce reflections on post Covid-19 crisis trends for the Creative Economy sector. The main argument is that the trends have changed due to coronavirus pandemic, causing a strong global economic crisis. For this purpose, a desk research was carried out - both bibliographical, regarding the central themes, for the construction of the theoretical reflection presented, and of documents (newspaper and magazine articles) about the Covid-19 pandemic impact on the Creative Economy sector and alternatives that Brazilian and foreign entrepreneurs had to find in order to circumvent the crisis caused by Covid-19 Keywords: creative economy, Covid-19, pandemic, crisis, trends